(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The reason we focus on this concept in this book is because information is an important part of GAT, or without it, GAT would be meaningless. We can call it information in our ordinary language, but if we say it in the language of GAT, then this concept has a slightly wider meaning. We know that in the world of information there are 2 different concepts, one is information and the other is information. Information is the event we see, and information is the image of that event processed in the human mind. In GAT, information is derived from the processing of primary data obtained from the place, unlike the above definition, this information or primary information is not in the human mind, it is processed using special programs of GAT and stored in the database, and in the future, depending on the user’s desire, it is presented in the form of electronic or ordinary paper.